2008
DOI: 10.2174/157016308784746274
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Study of Cyclodextrins Complexation with Benzimidazolic Antihelmintics in Different Reaction Media

Abstract: The main purpose of this work was to accomplish a comparative study about cyclodextrins complexation equilibria with three benzimidazolic antihelmintics: albendazole (Alb), mebendazole (Meb) and thiabendazole (Thiab). The complexation process with four different cyclodextrins (alpha-, beta-, gamma-, and HP-beta-CDs) was investigated under various temperatures and different reaction media (aqueous solution buffered at pH 7.5, dimethylsulfoxide (DMSO) and DMSO/water at 25/75, 50/50, 75/50 (w/w) mixtures). It was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…The H3 and H5 signals also showed chemical shifts, which confirmed inclusion, as these signals correspond to the internal protons of the NSs. These results are consistent with previous studies with native CDs and NSs [10,[30][31][32][33][34].…”
Section: H-nmr Spectra Of Ns-dtf Inclusion Compoundsupporting
confidence: 93%
See 1 more Smart Citation
“…The H3 and H5 signals also showed chemical shifts, which confirmed inclusion, as these signals correspond to the internal protons of the NSs. These results are consistent with previous studies with native CDs and NSs [10,[30][31][32][33][34].…”
Section: H-nmr Spectra Of Ns-dtf Inclusion Compoundsupporting
confidence: 93%
“…As NSs are insoluble in deuterated water/chloroform, deuterated DMSO was used as a solvent for the 1 H-NMR analyses. Previous studies have shown that DMSO does not interfere with the formation of the inclusion compound [10,[30][31][32][33][34]. As seen in Figure 3, 1 H-NMR spectra show that some of the signals in the NS-DTF complex are sharper than that of NSs alone.…”
Section: H-nmr Spectra Of Ns-dtf Inclusion Compoundmentioning
confidence: 71%
“…In some cases, a high concentration of DMSO can prevent a complexation from taking place, like for the binding of puerarin with β-CD, which does not occur at 100% DMSO. 20 Finally, Bernad-Bernad et al 19 showed that the binding constant of albendazole and mebendazole to α, β-, and γ-CD drastically decreases when 25%, 50%, or 75% DMSO is added, but at 100% DMSO, if the binding constant is smaller than that in water it is larger than that in a mixture of water and DMSO. However, the behavior is different for thianedazole: while additions of DMSO continuously increase the binding constant for β-CD, it first increases it for α- and γ-CD at 36% and 50% DMSO and then decreases it for 75% and 100%.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the effect of a few percent of DMSO on the binding of chemically unmodified cyclodextrins has never been investigated. All previous studies dealt with large concentrations, ranging from 25% to 100% DMSO. …”
Section: Introductionmentioning
confidence: 99%
“…Some binding studies of guests by CDs in nonaqueous or mixed organic–aqueous solvents have been reported. Organic solvent systems studied include DMSO, , DMF, , mixed alcohol–water, and various other organic solvents . In all these studies, a significant decrease of the binding constant for a specific guest was observed in organic solvents as compared to aqueous solvent, or upon increase in organic solvent proportion in organic–aqueous solvent mixtures.…”
Section: Introductionmentioning
confidence: 99%